Early postoperative arterial lactate concentrations to stratify risk of post-hepatectomy liver failure. Issue 11 (25th October 2021) - Niederwieser, Thomas; Braunwarth, Eva; Dasari, Bobby V M; Pufal, Kamil; Szatmary, Peter; Hackl, Hubert; Haselmann, Clemens; Connolly, Catherine E; Cardini, Benno; Öfner, Dietmar; Roberts, Keith; Malik, Hassan; et al.
Abstract: Background: Post-hepatectomy liver failure (PHLF) represents the major determinant for death after liver resection. Early recognition is essential. Perioperative lactate dynamics for risk assessment of PHLF and associated morbidity were evaluated. Methods: This was a multicentre observational study of patients undergoing hepatectomy with validation in international high-volume units. Receiver operating characteristics analysis and cut-off calculation for the predictive value of lactate for clinically relevant International Study Group of Liver Surgery grade B/C PHLF (clinically relevant PHLF (CR-PHLF)) were performed. Lactate and other perioperative factors were assessed in a multivariable CR-PHLF regression model. Results: The exploratory cohort comprised 509 patients. CR-PHLF, death, overall morbidity and severe morbidity occurred in 7.7, 3.3, 40.9 and 29.3 per cent of patients respectively. The areas under the curve (AUCs) regarding CR-PHLF were 0.829 (95 per cent c.i. 0.770 to 0.888) for maximum lactate within 24 h (Lactate_Max) and 0.870 (95 per cent c.i. 0.818 to 0.922) for postoperative day 1 levels (Lactate_POD1). The respective AUCs in the validation cohort (482 patients) were 0.812 and 0.751 and optimal Lactate_Max cut-offs were identical in both cohorts. Exploration cohort patients with Lactate_Max 50 mg/dl or greater more often developed CR-PHLF (50.0 per cent) than those with Lactate_Max between 20 and 49.9 mg/dl (7.4 per cent) or less than 20 mg/dl (0.5 per cent; P < 0.001). This also applied to death (18.4, 2.7 and 1.4 per cent), severe morbidity (71.1, 35.7 and 14.1 per cent) and associated complications such as acute kidney injury (26.3, 3.1 and 2.3 per cent) and haemorrhage (15.8, 3.1 and 1.4 per cent). These results were confirmed in the validation group. Combining Lactate_Max with Lactate_POD1 further increased AUC (ΔAUC = 0.053) utilizing lactate dynamics for risk assessment. Lactate_Max, major resections, age, cirrhosis and chronic kidney disease were independent risk factors for CR-PHLF. A freely available calculator facilitates clinical risk stratification (www.liver-calculator.com ). Conclusion: Early postoperative lactate values are powerful, readily available markers for CR-PHLF and associated complications after hepatectomy with potential for guiding postoperative care. Presented in part as an oral video abstract at the 2020 online Congress of the European Society for Surgical Research and the 2021 Congress of the Austrian Surgical Society. Lay Summary: Liver failure represents a major complication after liver resection and determines the risk of postoperative death, therefore early anticipation and risk stratification are highly relevant. This study, of 991 patients in three international centres, shows that the maximum lactate blood level within 24 h after surgery is a very strong factor predicting the further course after liver operations. Lactate could potentially aid in clinical decision making such as prophylactic treatment, intensified observation or early discharge of patients. Abstract : Liver failure represents a major complication after liver resection and determines the risk of postoperative death, therefore early anticipation and risk stratification are highly relevant. This study, of 991 patients in three international centres, shows that the maximum lactate blood level within 24 h after surgery is a very strong factor predicting the further course after liver operations. Lactate could potentially aid in clinical decision making such as prophylactic treatment, intensified observation or early discharge of patients.